A Formal Comparison of Advanced Digital Signature Primitives - Schürmann, Patrick

Weiterentwicklung der induktiven Schnellhärtung von Klebverbindungen für robuste Fertigungsprozesse unter Berücksichtigung von serienrelevanten Einflussfaktoren - Kowatz, Jannik; Teutenberg, Dominik; Meschut, Gerson (23. Kolloquium Gemeinsame Forschung in der Klebtechnik)

Morphological and mechanical properties of foamed thick-walled Wood-Plastic-Composite structures - Moritzer, Elmar; Flachmann, Felix (Journal of Cellular Plastics)
Microcellular wood fiber reinforced polymers offer the possibility to reduce the use of fossil raw materials. In particular, thick-walled structures with thicknesses greater than 6 mm offer a high potential for weight savings. This study investigates the cell structures and mechanical properties of injection-molded test specimens. The influence of different thicknesses (6–10 mm) along with different chemical blowing agents (endothermic, exothermic) with varying dosages (0–2 wt%) is analyzed. The investigations reveal that exothermic chemical blowing agents form finer cells consistently to thin-walled structures than endothermic ones. Higher foaming agent content leads to higher pore fractions, with many small cells coalescing into a large open-pore cell network. The mechanical properties depend mainly on the pore content of the sample. The specific tensile properties deteriorate with the use of chemical blowing agents (CFA), whereas the sandwich structure produced with compact edge layers has a positive influence on the specific flexural properties.
Keywords: Materials Chemistry; Polymers and Plastics; General Chemistry

Distribution Network Optimization: Predicting computation times to design scenario analysis for network operators - Burmeister, Sascha Christian; Schryen, Guido (Energy Systems)

Energy and Resource-efficient Forming of Gas Cylinders by Friction-Spinning - Dahms, Frederik; Homberg, Werner (Materials Research Proceedings)
Abstract. Friction-spinning as an innovative incremental forming process enables large degrees of deformation in tube and sheet metal-forming due to a self-induced heat generation in the forming zone. This paper presents new process designs for energy and resource-efficient forming of gas cylinders by friction-spinning without the use of an external heat supply. The self-generated heat enables friction-spinning process to reduce the energy demand in the manufacture of gas cylinders, which are usually manufactured with external heat (mostly fossil fuels), by 95 %. Typical gas cylinder contours, such as flattened and spherical bottom ends and cylinder necks, are manufactured by friction-spinning of AW 6060 tubular profiles with specifically designed tool path strategies. It is shown that friction-spinning enables the manufacture of typical gas cylinder contours with sufficient wall thickness and the required gas tightness without the input of external heat. Thus, this process can contribute to an increase in the energy and resource efficiency of forming processes.

Thermal conductivity of solid paraffins and several n-docosane compounds with graphite - Paul, Andreas; Baumhögger, Elmar; Dewerth, Mats-Ole; Hami Dindar, Iman; Sonnenrein, Gerrit; Vrabec, Jadran (Journal of Thermal Analysis and Calorimetry)
The technical importance of paraffins as phase change materials (PCM) in heat storage systems increases. Knowledge on the thermal conductivity of paraffins is necessary for the design and optimization of heat storage systems. However, for most paraffins solely the thermal conductivity of the liquid state has been sufficiently investigated. For the solid state, precise thermal conductivity data are only known for a few paraffins, while only generalized values are available for the remainder, some of which contradict each other. In this study, a measurement setup based on the modified guarded hot plate method is developed. It is used to investigate the thermal conductivity of several paraffines in the solid state, including pure n-docosane and its compounds with different types and concentrations of graphite. For n-docosane in the solid state, the thermal conductivity is determined to be 0.49 W/(m K). A particle size of 200 μm with a spherical shape turns out to be optimal to increase the thermal conductivity. This allows the thermal conductivity of a compound with 10% graphite to increase by a factor of three compared to the pure paraffin. Furthermore, significant differences to thermal conductivity data from the literature are found.
Keywords: Physical and Theoretical Chemistry; Condensed Matter Physics

Alterungsmechanismen von Haushaltskältegeräten - Paul, Andreas; Baumhögger, Elmar; Elsner, Andreas; Reineke, Michael; Kasper, Tina; Schumacher, Daniel; Vrabec, Jadran; Hüppe, Christian; Stamminger, Rainer; Hölscher, Heike; Stoll, Ragnar; Wagner, Hendrik; et al.
Die für die Berechnung des Energieeffizienzindex von Haushaltskältegeräten benötigten Parameter werden durch Norm-Messungen im Neuzustand der Geräte bestimmt. Aus früheren Untersuchungen ist bekannt, dass durch verschiedene technische Alterungsmechanismen der Energieverbrauch über eine Produktlebensdauer von 18 Jahren um bis zu 33 % zunehmen kann. Ziel des vom BMWi geförderten Projekts ALGE war es, die verschie-denen Ursachen und Einflussgrößen für die Alterung von Haushaltskältegeräten zu ermitteln und eine Alterungs-funktion zu bestimmen, die den zeitlichen Verlauf des zunehmenden Energieverbrauchs beschreibt. In diesem Projekt wurde das Alterungsverhalten von Haushaltskältegeräten durch 100 Normenergieverbrauchs-messungen an 32 real gealterten Geräten untersucht. Aus den gewonnenen Ergebnissen konnte eine Alterungs-funktion bestimmt werden, die den Anstieg des Energieverbrauchs beschreibt. Alle untersuchten Geräte wurden an der Universität Paderborn im Neuzustand vermessen und nach einer Laufzeit von bis zu 21 Jahren erneut geprüft. Bereits nach einem zweijährigen Betrieb konnte ein Mehrverbrauch von bis zu 11 % festgestellt werden. Über die durchschnittliche Produktlebensdauer von Haushaltskältegeräten von ca. 16 Jahren steigert sich der Energieverbrauch um durchschnittlich 27 %. Im Rahmen des Projekts wurden verschiedene Systemkomponenten, wie Isolierung und Verdichter, hinsichtlich ihres Alterungsverhaltens untersucht. Bei dem im Gehäuse als Isolierung verwendeten PUR-Schaum konnte über einen Zeitraum von 31 Monaten ein Anstieg der Wärmeleitfähigkeit von 19,5 W/(m⋅K) auf 24,5 W/(m⋅K) festge-stellt werden. Zur Untersuchung der Alterung der Verdichter wurden zuvor auf einem Kalorimeterteststand ver-messene Verdichter in Geräte eingebaut. Nach einem zweijährigen Betrieb wurden diese Verdichter wieder aus-gebaut und erneut vermessen. Hierbei konnte keine Änderung des COP festgestellt werden. Zusätzlich zu den technischen Parametern wurde der Einfluss des Verbraucherverhaltens analysiert. Hier zeigte sich, dass bis zu 33 % des Gesamtenergieverbrauchs nach einer mehrjährigen Nutzungsdauer verbraucherinduziert sein können.
Keywords: Haushaltskältegeräte; Energieverbrauch; Alterung; Verdichter; PUR-Schaum

Development of an adaptive coaxial concrete rheometer and rheological characterisation of fresh concrete - Josch, Sebastian; Jesinghausen, Steffen; Schmid, Hans-Joachim (Applied Rheology)
Abstract The accessibility to rheological parameters for concrete is becoming more and more relevant. This is mainly related to the constantly emerging challenges, such as not only the development of high-strength concretes is progressing very fast but also the simulation of the flow behaviour is of high importance. The main problem, however, is that the rheological characterisation of fresh concrete is not possible via commercial rheometers. The so-called concrete rheometers provide valuable relative values for comparing different concretes, but they cannot measure absolute values. Therefore, we developed an adaptive coaxial concrete rheometer (ACCR) that allows the measurement of fresh concrete with particles up to d max = 5.5 mm {d}_{{\rm{\max }}}=5.5\hspace{.5em}{\rm{mm}} . The comparison of the ACCR with a commercial rheometer showed very good agreement for selected test materials (Newtonian fluid, shear thinning fluid, suspension, and yield stress fluid), so that self-compacting concrete was subsequently measured. Since these measurements showed a very high reproducibility, the rheological properties of the fresh concrete could be determined with high accuracy. The common flow models (Bingham (B), Herschel–Bulkley, modified Bingham (MB) models) were also tested for their applicability, with the Bingham and the modified Bingham model proving to be the best suitable ones.
Keywords: Condensed Matter Physics; General Materials Science

Please Mind the Gap. Reconfiguring Solidarity through Space in Michael Nicoll Yahgulanaas' Haida Manga Art. - Jende, Yvonne Kristin (Solidarités. Réseaux – Convivialités – Confrontations/ Solidarities. Networks – Convivialities – Confrontations, 44. Annual Conference of the Association for Canadian Studies in German-Speaking Countries)

Flowability of polymer powders at elevated temperatures for additive manufacturing - Rüther, Moritz Johannes; Klippstein, Sven Helge; Ponusamy, SathishKumar; Rüther, Torben; Schmid, Hans-Joachim (Powder Technology)
Keywords: General Chemical Engineering

Thermal influence of resistance spot welding on a nearby overmolded thermoplastic–metal joint - Wippermann, Jan; Meschut, Gerson; Koschukow, Wikentji; Liebsch, Alexander; Gude, Maik; Minch, Steven; Kolbe, Björn (Welding in the World)
Keywords: Metals and Alloys; Mechanical Engineering; Mechanics of Materials

Influence of plasma coating pretreatment on the adhesion of thermoplastics to metals - Wippermann, Jan; Koshukow, Wikentij; Liebsch, Alexander; Kolbe, Björn; Meschut, Gerson; Gude, Maik (Tagungsband Münchener Leichtbauseminar 2022)

Dynamisch-mechanische Polymerpartikelverrundung zur Verbesserung der Fließfähigkeit für das selektive Lasersintern - Ponusamy, SathishKumar; Schmid, Hans-Joachim

Tax Education After WWII: How Spain, the USA, and West Germany Tried to Make Their Citizens Pay Honestly - Schönhärl, Korinna; Düll, Nasrin; Ramírez Lugo , Nadya Melina (Tax Evasion and Tax Havens since the Nineteenth Century)
State education in honest tax payment can be understood as a facet of training in citizenship, i.e. as an attempt by the modern state to standardize the behavior of its citizens and to prevent deviations. Based on this Foucauldian understanding, this exploratory article examines tax education in the United States, Spain, and West Germany from the mid-1940s to the late 1980s. During this period, the USA asserted itself as the champion of tax education and Spain consistently tried to emulate this example, albeit with more modest means and different semantic strategies from as early as the 1960s, when it was still under a autoritarian regime. The FRG, however, completely discontinued its few early attempts at tax education from the mid-1950s onwards. Even during the economic crises and tax scandals of the 1970s, there was no relaunch of the programs. The article locates the reasons for this highly uneven development in the different ideal images of the citizen in the three states.

Feasibility Study of Compression Molding for Large Reinforcement Structures in the Commercial Vehicle Sector - Lückenkötter, Julian; Leimbach, J.P.; Stallmeister, Tim; Marten, Thorsten; Tröster, Thomas (Materials Research Proceedings)
Abstract. Due to an increasing volume of shipments, there is a significant need for more delivery vehicles. One approach to reduce the associated increase in carbon dioxide (CO2) emissions is a new light weight design approach involving the substitution of conventional materials with glass fiber mat-reinforced thermoplastics (GMT) based on polypropylene (PP). The application of GMT by compression molding is a widely used process in the automotive industry. However, application in the commercial vehicle sector requires much larger dimensions, making it necessary to clarify whether the manufacturing process and material are suitable for semi-structural applications on this scale. To find this out, two replacement geometries are abstracted in this study and manufactured by varying the main manufacturing parameters. The feasibility can be demonstrated by recording and analyzing the resulting process variables and measuring the formed fiber distribution. At the end of the paper, recommendations are given for the production of GMT structures on the scale of commercial vehicles.
Keywords: Compression Molding; Fiber Content; Process Development; Lightweight Design

Selective Discrimination between CO and H2 with Copper–Ceria-Resistive Gas Sensors - Baier, Dominik; Priamushko, Tatiana; Weinberger, Christian; Kleitz, Freddy; Tiemann, Michael (ACS Sensors)
The production of hydrogen and the utilization of biomass for sustainable concepts of energy conversion and storage require gas sensors that discriminate between hydrogen (H2) and carbon monoxide (CO). Mesoporous copper–ceria (Cu–CeO2) materials with large specific surface areas and uniform porosity are prepared by nanocasting, and their textural properties are characterized by N2 physisorption, powder XRD, scanning electron microscopy, transmission electron microscopy, and energy-dispersive X-ray spectroscopy. The oxidation states of copper (Cu+, Cu2+) and cerium (Ce3+, Ce4+) are investigated by XPS. The materials are used as resistive gas sensors for H2 and CO. The sensors show a stronger response to CO than to H2 and low cross-sensitivity to humidity. Copper turns out to be a necessary component; copper-free ceria materials prepared by the same method show only poor sensing performance. By measuring both gases (CO and H2) simultaneously, it is shown that this behavior can be utilized for selective sensing of CO in the presence of H2.
Keywords: Fluid Flow and Transfer Processes; Process Chemistry and Technology; Instrumentation; Bioengineering

Proof of concept for incremental sheet metal forming by means of electromagnetic and electrohydraulic high-speed forming - Holzmüller, Maik; Linnemann, Maik; Homberg, Werner; Psyk, Verena; Kräusel, Verena; Kroos, Janika (Materials Research Proceedings)
Abstract. The combination of incremental sheet metal forming and high-speed forming offers new possibilities for flexible forming processes in the production of large sheet metal components of increased complexity with relatively low forming energies. In this paper, the general feasibility and process differences between the pulse-driven high-speed forming technologies of electrohydraulic and electromagnetic forming were investigated. An example component made of EN AW 6016 aluminum sheet metal was thus formed incrementally by both processes and the forming result evaluated by an optical 3D measurement system. For this purpose, a forming strategy for electromagnetic incremental forming (EMIF) was developed, tested and adapted to the electrohydraulic incremental forming process (EHIF). The discharge energy, the tool displacement and the pressure field of the forming zone were determined as relevant parameters for the definition of an adequate tool path strategy. It was found that the EHIF process is less affected by larger distances between the tool and the blank, while this is a critical variable for force application to the component during EMIF. On the other hand, the more uniform pressure distribution of the EMIF process is advantageous for forming large steady component areas.
Keywords: Incremental Sheet Forming; Aluminium; High-Speed Forming

Investigation of Pressure Fields Generated by Two Simultaneous Discharges in Liquid Initiated by Wires - Knyazyev, Mykhaylo; Holzmüller, Maik; Homberg, Werner (Journal of Manufacturing and Materials Processing)
The pressure fields generated by two simultaneous discharges have not been investigated on any notable scale for the electrohydraulic impulse forming method. In this study, the synchronicity of two discharges is ensured by the sequential connection of two wires mounted in two spark gaps in a common volume of liquid. The objective is to experimentally confirm the equilibrium of the energies evolved in two spark gaps by means of pressure measurements. In addition, multipoint membrane pressure gauges demonstrated the feasibility of easily recording detailed pressure maps. Based on the membrane deformation mechanism and material strengthening under static and impulse conditions, the processing procedure is further developed so as to achieve better accuracy in the determination of pressure field parameters. The practical equality of the pressure fields on the left and right halves of the flat-loaded area confirms the equality of energies evolved in the two spark gaps. The direct shock waves create zones with the most intensive loading. These results provide a basis for the development of new electrohydraulic technologies involving the application of two simultaneous discharges with equal energy and pressure parameters.
Keywords: impulse; forming; electrohydraulic; discharge; wire; pressure gauge; pressure field

Studien zu Schulleistungen und ihre Aufbereitung - Neumann, Phillip (Zeitschrift für Heilpädagogik)
Keywords: Inklusion; Sonderpädagogik; Bildung; Bildungsstudien; Integration

Wässrige Glucosaminlösung als neues Lösungsmittel zur CO2-Abscheidung - Hami Dindar, Iman; Lutters, Nicole; Kenig, Eugeny (Jahrestreffen der ProcessNet-Fachgruppen Fluidverfahrenstechnik und Adsoprtion)